APPLICATION OF THE PRINCIPLE OF TRANSPARENCY IN PUBLIC INFORMATION SERVICES: STUDY OF THE OFFICE OF COMMUNICATION, INFORMATION AND STATISTICS (KOMINFO) BARRU REGENCY - Masyitah (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal